The BargainEl-MessidiKathy Groehn. The Bargain. New York: Nellen, 1980, 120 pp., $8.95. - Jackson, John H. (Academy of Management Review, 1981)
The article reviews the book ?The Bargain,? by Kathy Groehn El-Messidi.